CHEMICAL ANALYSIS DURING THE PROCESSING OF DRIED SALTED ANCHOVY - Eko Nurcahya Dewi (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Dried salted  anchovy is a rich source of  protein which is processed by boiling, salting and drying. During processing the protein undergoes change, e.g. protein myofibril  becomes denatured to some extent , and it can be visualised using SDS-PAGE protein pattern. Protein can also react with lipid to form brown colour mainly in  high temperature. The result of the analyses shown that there were differences in proximate composition between different samples of  anchovy. There were not much difference in sample band pattern for fresh , boiled ,  boiled and dried anchovy samples. The highest solubility protein was found in the Indonesian dried salted anchovy while the lowest was in fresh sample. The colour of boiled sample was the  whitest in comparison to fresh, boiled and dried, Indonesian dried salted anchovy and Japanese boiled. Except for Indonesian dried salted anchovy,  brown colour and development of  lipid oxidation was not detected.